Revision of the Megaloptera (Insecta: Neuropterida) of Madagascar - Liu, Xingyue; Price, Benjamin W.; Hayashi, Fumio; de Moor, Ferdinand; Yang, Ding (Zootaxa, 2014)
The Megaloptera fauna of Madagascar comprise two endemic genera: Haplosialis Navás, 1927 (Sialidae) and Madachauliodes Paulian, 1951 (Corydalidae: Chauliodinae). Here the two genera are revised, with detailed descriptions and illustrations. A new species, Madachauliodes bicuspidatus Liu, Price & Hayashi, sp. nov., is described. Furthermore the phylogeny and biogeography of the Madagascan fauna is discussed.